Penerapan Metode K-Means Clustering Dalam Mengetahui Minat Siswa Terhadap Mata Pelajaran Matematika Di SMP Negeri 19 Kota Bengkulu - Murni Tiana; Siswanto Siswanto; Indra Kanedi (Jurnal Media Infotama, 2024)
Junior High School 19 Bengkulu City is one of the public junior high schools in Bengkulu City. In this school there is a Mathematics subject that is taught to students. Students' ability to understand the subject varies, so that sometimes it is difficult for teachers when the learning process is taking place. Interest in learning tends to produce high achievement, on the other hand, lack of interest in learning will result in low achievement and there are differences in interest in each subject. The implementation of K-Means Clustering Method in knowing students’ interest in mathematics subjects at Junior High School 19 Bengkulu City can make it easier for teachers to find out students’ interest and can be used as material for teacher evaluation in teaching and learning process in order to create high interest in subjects, especially mathematics. Based on the sample data used in class VIII.E on mathematics subject with 10 students in the odd semester of the 2023/2024 school year. The results of grouping students who fall into cluster C1 (very interested) are 4 students, while students who fall into cluster C2 (less interested) are 6 students. If it is percented, the Cluster C1 result is 60%.